Educational inequality across three generations in Australia. Issue 1 (26th March 2018) - Hancock, Kirsten J.; Mitrou, Francis; Povey, Jenny; Campbell, Alice; Zubrick, Stephen R.
Abstract: The transfer of advantage and disadvantage across multiple generations is receiving increasing attention in the international literature; however, transfers of resources across multiple generations in Australian families are less well understood. Using a longitudinal dataset of Australian children, we have the opportunity to not only investigate the transfer of educational resources across three generations in Australia, but also investigate the gendered nature of these transfers, which has been a limitation of other studies. We find no evidence of individual grandparent education effects on numeracy and reading scores for grandchildren in Year 3, independent of parent educational attainment and other covariates. However, significant effects on numeracy and reading scores were observed for children in families where both the grandmother and grandfather in maternal and paternal grandparent sets had high educational attainment (a diploma or university qualification), and where either or both the mother and father had a university qualification. These results suggest that the contribution of grandparents to the academic achievement of grandchildren cannot be fully explained by the parent generation and that the concentration of human capital in families contributes to educational inequalities across multiple generations that can be observed by eight years of age.